Photovoltaic Characteristics of Solar Cells Based on Nanostructured Titanium Dioxide Sensitized with Fluorescein Sodium Salt - Farooq, W. A.; Fatehmulla, Amanullah; Yakuphanoğlu, Fahrettin; Yahia, I. S.; Ali, Syed Mansoor; Atif, M.; Tawfik, Walid (Springer, 2014)
We have designed solar cells based on nanostructured titanium dioxide sensitized by fluorescein sodium salt, and we have studied their photovoltaic and impedance characteristics. Under AM1.5 illumination and optimal conditions, an open-circuit photovoltage of 0.56 V and a short-circuit current density of 72 mu A/cm(2) were achieved. An impedance spectroscopy study of the voltage dependence of the capacitance in the frequency range 2-5 kHz did not reveal any shift from positive to negative capacitance.
Keywords: fluorescein sodium salt; solar cell; photovoltaic; nanostructure